Pengaruh Strategy Coping Terhadap Flourishing Dengan Self-Compassion Sebagai Perantara Pada Penderita Dyspepsia Fungsional - Rusda Parinduri; Suryani Hardjo; Salamiah Sari Dewi (Indonesian Counselor Association (IKI), 2025)
Teachers often experience prolonged work-related stress that can negatively affect psychological well-being and physical health, including functional dyspepsia. This study aimed to examine how teachers achieve flourishing despite significant work stress, with a focus on coping strategies and the role of self-compassion as an internal psychological mechanism. Specifically, this study investigated the effect of coping strategies on flourishing, the effect of coping strategies on self-compassion, the effect of self-compassion on flourishing, and the mediating role of self-compassion in the relationship between coping strategies and flourishing among teachers with functional dyspepsia. A quantitative approach was employed by distributing self-report scales to 200 teachers who met the criteria of the R4-FDDQ Functional Dyspepsia screening test. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with JASP version 0.19.3.0. The results indicated that the data met validity and reliability requirements and that the proposed model demonstrated a good fit. Coping strategies were found to have a significant effect on flourishing and self-compassion. However, self-compassion did not significantly influence flourishing and did not function as a mediating variable between coping strategies and flourishing. In addressing problems, teachers with functional dyspepsia tended to prioritize religious coping and mindfulness over other indicators. Nevertheless, the common humanity dimension of self-compassion appeared to be inconsistent with flourishing, as prolonged illness contributed to feelings of isolation and hindered the development of positive social connections.